Clinical and molecular cytogenetic (FISH) diagnosis of Williams syndrome. Issue 1 (January 1996) - Brewer, C M; Morrison, N; Tolmie, J L
Abstract : Sixteen children and adolescents with a firm clinical diagnosis of Williams syndrome were investigated with the chromosome fluorescence in situ hybridisation (FISH) technique employing the elastin gene probe. In each case there was a fluorescent signal on one chromosome 7 homologue only, indicating elastin gene deletion. No deletion was demonstrated in another child in whom an earlier diagnosis of Williams syndrome was judged doubtful at review. Firm clinical diagnosis correlates with elastin gene deletion in 16/16 cases of Williams syndrome and detection of such hemizygosity by FISH constitutes a useful confirmatory diagnostic test.